Exploring the effect of combined hydrothermal-microwave pretreatment operating conditions on canola oil expression - Cortese, C. M. (2017)
The effect of the combined hydrothermal-microwave (HT-MW) pretreatment operating conditions on the oil extraction yield by cold pressing was evaluated, as well as its canolol and tocopherols content. Entire and broken canola seeds were subjected to hydrothermal pretreatment at different temperatures (110°C and 130°C), then they were irradiated in a microwave oven until reaching a moisture content of 6.5% (dry basis), that it is a safe storage moisture and it is adequate for the pressing process. Entire seeds exposed at a HT temperature of 130°C and microwaved for 2.98 min exhibited the best canola oil expression yield (34.9%, d.b) and the highest amount of canolol (533 μg/g oil), maintaining the total tocopherol content invariant with respect to oil from samples subjected tothe other pretreatment operating conditions and from untreated seeds. However, individual tocopherol isomers presented different contents when varying pretreatment conditions, showing a differential extraction due to the factors analysed (seeds granulometry/breakage and HT temperature). At the optimum conditions quality as means of acidity, peroxide index and p-Anisidine value were determined. Acidity index slightly increased due to the pretreatment and peroxide index significantly diminished, being both value below the limits preestablished by the Alimentarius Codex. Meanwhile, p-Anisidine value notably increased, slightly affecting TOTOX value.